Siblings sit on the deck of the ship, City of New York (Philadelphia Evening Bulletin, 1930)
"At the left are ten-year-old Alice Jean Phipps and her brother, Richard, thirteen, on the City of New York today at the Callowhill st. wharf. Alice has on Captain Ashley C. McKinley's Arctic gloves, and Richard-well today is his birthday-and He's celebrating in the fur parka worn by Captain McKinley when he was in Antarctica with Admiral Byrd's band of explorers." With clipping